2020
DOI: 10.2147/cmar.s259393
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of the Up-Regulation of Circular RNA Hsa_circ_0069767 Derived from C-KIT on the Biological Behavior of Multiple Myeloma Cells</p>

Abstract: Purpose: Multiple myeloma (MM) is an incurable disease. This study focused on the expression of circular RNA circ_0069767 in MM and its influence on prognosis, in order to provide a potential target. Patients and Methods: Totally 66 MM patients participated in this research. Using RT-PCR method to determine the expression level of circ_0069767 in 66 sorted samples from multiple myeloma patients and 21 normal control bone marrow samples, Kaplan-Meier was applied for survival analysis. We constructed stable over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…Therefore, it is crucial to investigate the potential pathogenic mechanisms of the occurrence and development of MM, especially in terms of proliferation and apoptosis in order to develop new treatment strategies ( 1 ). In recent years, the use of non-coding RNAs (including miRNAs, long non-coding RNAs, circular RNAs, and siRNA) has become increasingly popular for studying the mechanisms and treatments of MM ( 23 , 24 ). This present study demonstrated that miR-19a-3p was significantly down-regulated in MM patients and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial to investigate the potential pathogenic mechanisms of the occurrence and development of MM, especially in terms of proliferation and apoptosis in order to develop new treatment strategies ( 1 ). In recent years, the use of non-coding RNAs (including miRNAs, long non-coding RNAs, circular RNAs, and siRNA) has become increasingly popular for studying the mechanisms and treatments of MM ( 23 , 24 ). This present study demonstrated that miR-19a-3p was significantly down-regulated in MM patients and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of circ_0069767 was remarkably higher in MM patients than in healthy subjects, but MM subjects with higher expression of circ_0069767 had longer PFS and OS, as if the increased presence of the circRNA caused a reduction of growth and diffusion and increased programmed cell death; moreover, knockdown of circ_0069767 provoked the opposite biological effects. As far as the mechanisms via circ_0069767 exert their actions, it was demonstrated that this circRNA, by sponging miRNA-636 in MM cells, controls cell generation [ 71 ].…”
Section: Circrnas and Multiple Myelomamentioning
confidence: 99%
“…Meanwhile, circRNAs have been shown to regulate the invasion and migration of cells and further promote the progression of hematological malignancies, such as overexpressing circ-0069767 decreases the invasion and migration capacities of MM cells by sponging miR-636 to regulate the expression of K-RAS [72], whereas circ-0000142 enhances the invasion of MM cells via the circ-0000142/miR-610/AKT3 axis [73], etc.…”
Section: Circrnas Regulate the Proliferation Apoptosis Cell Cycle Inv...mentioning
confidence: 99%